Use of laser technologies and intense pulsed light in the treatment of exogenous ochronosis: a literature review - Pedro de Freitas Silva Torraca; Estela Mari Sandini; Tania Christina Marchesi de Freitas (Sociedade Brasileira de Dermatologia (SBD), 2021)
Exogenous ochronosis is a cutaneous hyperpigmentation condition caused by the accumulation of substances derived from phenol on the skin or mucous membranes without affecting other tissues. It occurs mainly due to the use of bleaching agents, most frequently hydroquinone. The lesions are difficult to treat, being resistant to several approaches. Sometimes it's necessary to use laser technologies or intense pulsed light to achieve some degree of improvement. The present work consists of a literature review of publications on these technologies in exogenous ochronosis from January 1990 to July 2020.